In the event of a variable text. (February 2017) - Carpenter, JR
Walter J Ong argues: 'The spoken word is always an event, a movement in time, completely lacking in the thing-like repose of the written or printed word'. Digital writing has given rise to a new regime of enunciation in which written words refuse repose. This essay argues that although spoken, written and printed words operate within radically different temporal planes, spoken words also have thing-like properties and written and printed words also move through time. Digital writing has given rise to a new regime of signification unforeseen by Ong in which written words refuse repose. Jay David Bolter argues that digital writing 'challenges the logocentric notion that writing should be merely the servant of spoken language…The writer and reader can create and examine structures on the computer screen that have no easy equivalent in speech'. N Katherine Hayles argues that, in digital media, the text 'becomes a process, an event brought into existence when the program runs…The [text] is "eventilized, " made more an event and less a discrete, self-contained object with clear boundaries in space and time'. Jean-Jacques Lecercle argues that language is a constructed system, constantly subject to change…'We therefore need to conceive of language not as a stable, arrested system, but as a system of variations'. This essay draws upon a diverse corpus of literary, media and performance theory and practice to establish a critical framework for examining the performance of variable texts throughout the entire apparatus of hardware, software, networks, bodies and spaces within and through which they operate and propagate. This framework is applied to a number of examples of digital writing which incorporates variability, instability, transformation and change into the process of composition, resulting in texts which are both physical and digital, confusing and confound boundaries between speaking, writing and reading.